Association of the ANRS-12126 Male Circumcision Project with HIV Levels among Men in a South African Township: Evaluation of Effectiveness using Cross-sectional Surveys - Auvert, Bertran (Public Library of Science, 2013)
BACKGROUND: Randomized controlled trials have shown that voluntary medical male circumcision (VMMC) reduces HIV infection by 50% to 60% in sub-Saharan African populations; however, little is known about the population-level effect of adult male circumcision (MC) as an HIV prevention method. We assessed the effectiveness of VMMC roll-out on the levels of HIV in the South African township of Orange Farm where the first randomized controlled trial (RCT) to test the effect of VMMC on HIV acquisition was conducted in 2002–2005. METHODS AND FINDINGS: The Bophelo Pele project is a community-based campaign against HIV, which includes the roll-out of free VMMC. A baseline cross-sectional biomedical survey was conducted in 2007–2008 among a random sample of 1,998 men aged 15 to 49 (survey response rate 80.7%). In 2010–2011, we conducted a follow-up random survey among 3,338 men aged 15 to 49 (survey response rate 79.6%) to evaluate the project. Participants were interviewed, blood samples were collected and tested for HIV and recent HIV infection (using the BED HIV incidence assay), and MC status was assessed through a clinical examination. Data were analyzed using multivariate and propensity statistical methods. Owing to the VMMCs performed in the context of the RCT and the Bophelo Pele project, the prevalence rate of adult MC increased from 0.12 (95% CI 0.10–0.14) to 0.53 (95% CI 0.51–0.55). Without these VMMCs, the HIV prevalence rate in 2010–2011 would have been 19% (95% CI 12%–26%) higher (0.147 instead of 0.123). When comparing circumcised and uncircumcised men, no association of MC status with sexual behavior was detected. Among circumcised and uncircumcised men, the proportion consistently using condoms with non-spousal partners in the past 12 months was 44.0% (95% CI 41.7%–46.5%) versus 45.4% (95% CI 42.2%–48.6%) with weighted prevalence rate ratio (wPRR) = 0.94 (95% CI 0.85–1.03). The proportion having two or more non-spousal partners was 50.4% (95% CI 47.9%–52.9%) versus 44.2% (95% CI 41.3%–46.9%) with wPRR = 1.03 (95% CI 0.95–1.10). We found a reduction of BED-estimated HIV incidence rate ranging from 57% (95% CI 29%–76%) to 61% (95% CI 14%–83%) among circumcised men in comparison with uncircumcised men. CONCLUSIONS: Findings suggest that the roll-out of VMMC in Orange Farm is associated with a significant reduction of HIV levels in the community. The main limitation of the study is that it was not randomized and cannot prove a causal association. The roll-out of VMMC among adults in sub-Saharan Africa should be an international priority and needs to be accelerated to effectively combat the spread of HIV. Please see later in the article for the Editors' Summary